Exercise as a modulator of gut microbiota for improvement of sleep quality: a narrative review - Zhao, Bin; Sun, Jinxiang; Xiang, Lijuan; Su, Zhanguo (Frontiers in Neuroscience, 2025)
Sleep quality is a cornerstone of physical and mental well-being, yet millions of individuals worldwide suffer from chronic sleep disturbances. Recent developments in microbiome research have shown that the microbiota–gut–brain axis regulates sleep by two-way communication between the gut and brain. Exercise is well-documented for its beneficial impact on sleep, yet emerging evidence indicates that one mechanism by which it achieves this may involve the modulation of gut microbiota. This narrative review examines the developing triadic relationship among exercise, gut microbiota, and sleep. It examines how exercise influences microbial diversity, the production of sleep-related metabolites like serotonin, GABA, and SCFAs, and immune responses that collectively shape sleep architecture. Additionally, the review highlights physiological factors influenced by exercise—such as gut motility, intestinal barrier function, and bile acid metabolism—that may impact the gut ecosystem and, in turn, sleep. Although encouraging results, deficiencies persist in our comprehension of the specific mechanisms connecting these domains. This review underscores the need for interdisciplinary research and suggests that targeting the gut microbiota via customized exercise interventions presents a promising, non-pharmacological strategy for enhancing sleep quality.